Peran Aplikasi Tiktok Dalam Transformasi Perilaku Mahasiswa - Nisa, Pia Khoirotun; Hana, Mutia; Azzahra, Syawla Malika; Prayoga, Muhammad Bintang; Az Zarkasyi, Jafar M.; M, Azka Aisul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
TikTok as a short video-based social media platform has become a global trend that affects various aspects of life, including student behavior. This research aims to analyze how the TikTok application contributes to changes in student behavior, both from the positive and negative sides. This research uses a qualitative approach with in-depth interview methods and content analysis to understand TikTok usage patterns. Research results reveal that TikTok plays a role in encouraging creativity, changing communication patterns, and influencing student lifestyles. However, this application also has a negative impact, such as the emergence of dependence, decreased productivity, and exposure to inappropriate content. This study emphasizes the importance of digital literacy to maximize the positive impact of using TikTok and reduce its negative impact. This finding is expected to be a guide for educational institutions and the community in responding to the development of social media wisely.